A randomized control led study comparing CMAC video laryngoscope and Macintosh laryngoscope for insertion of double lumen tube in patients undergoing elective thoracotomy - Amit Mathew; Jacob Chandy; Joseph Punnoose; Birla Roy Gnanamuthu; L Jeyseelan; Raj Sahajanandan (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Double lumen tube (DLT) insertion for isolation of lung during thoracic surgery is challenging and is associated with considerable airway trauma. The advent of video laryngoscopy has revolutionized the management of difficult airway. Use of video laryngoscopy may reduce the time to intubate for DLTs even in patients with normal airway. Material and Methods: A total of 87 ASA 1-3 adults, scheduled to undergo elective thoracotomy, requiring a DLT were randomly allocated to videolaryngoscope (CMAC) arm or Macintosh laryngoscope arm. It was on open label study, and only the patient was blinded. The primary objective of this study was to compare the mean time taken for DLT intubation with CMAC (Mac 3) and Macintosh laryngoscope blade and the secondary objectives included the hemodynamic response to intubation, the level of difficulty using the intubation difficulty scale (IDS), and complications associated with intubation. Data was analysed using the statistical software SPSS (version 18.0). Results: The time taken for intubation was not significantly different (42.8 ± 14.8 s for CMAC and 42.5 ± 11.5 s for Macintosh laryngoscope P -0.908). The CMAC video laryngoscope was associated with an improved laryngoscopy grade (Grade I in 81.8% with CMAC and in 46.5% with Macintosh), less pressure applied on the tongue, and less external laryngeal pressure required. Hemodynamic responses to intubation were similar in both groups. Conclusion: Macintosh blade is as good as CMAC (mac 3) blade to facilitate DLT intubation in adult patients with no anticipated airway difficulty, however CMAC was superior as it offers better laryngoscopic view, needed less force, and fewer external laryngeal manipulations.